2019
DOI: 10.1111/febs.14780
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA Crnde attenuates cardiac fibrosis via Smad3‐Crnde negative feedback in diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM)—ventricular dysfunction in the absence of underlying heart disease—is a common complication of diabetes and a leading cause of mortality associated with the disease. In DCM, cardiac fibrosis is the main cause of heart failure. Although it is well‐established that the transforming growth factor‐beta signaling pathway plays a part in inducing cardiac fibrosis in DCM, details of the molecular mechanism involved remain elusive. Therefore, it is crucial to study the gene reg;ulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Inhibited the binding of Smad3 to the α-SMA gene promoter via interacting with rSBEs DCM/Human, mouse/CFs Anti [199] miR-29 led to greater stability in the aortic walls, and prevented rupture by increasing the expression of several ECM genes, such as Col1A1, Col3A1, and elastin [170]. It is indicated that TGFβ could repress miR-29 expression under cardiac stress [154].…”
Section: Downmentioning
confidence: 99%
“…Inhibited the binding of Smad3 to the α-SMA gene promoter via interacting with rSBEs DCM/Human, mouse/CFs Anti [199] miR-29 led to greater stability in the aortic walls, and prevented rupture by increasing the expression of several ECM genes, such as Col1A1, Col3A1, and elastin [170]. It is indicated that TGFβ could repress miR-29 expression under cardiac stress [154].…”
Section: Downmentioning
confidence: 99%
“…Knockdown of MIAT in vivo reduced cardiac fibrosis, deregulated fibrosis genes, and restored heart function, suggesting MIAT is another potential therapeutic target to treat fibrosis. There are other examples of lncRNAs involved in cardiac fibrosis including n379519 [ 116 , 117 ], which promotes cardiac fibrosis by sponging miR-30 [ 88 ], and Crnde, which attenuates cardiac fibrosis in a negative feedback loop with Smad3 in diabetic cardiomyopathy [ 89 ].…”
Section: Lncrnas and Their Interventions In Heart Diseasementioning
confidence: 99%
“…Cardiovascular disease is a major cause of morbidity and mortality worldwide, especially for patients with diabetes (Tall and Levine, 2017; He et al, 2019; Tall and Jelic, 2019). Previous studies have reported that more than half of these patients die from diabetic cardiomyopathy (DCM), which is characterized by changes in myocardial structure and function such as ventricular hypertrophy, cardiac fibrosis, and heart failure (Ye et al, 2018; Kang et al, 2019; Knapp et al, 2019; Zheng et al, 2019). Due to the increased prevalence of DCM-related mortality, an understanding of the mechanism of DCM pathogenesis and effective therapies are needed urgently (Sun et al, 2019; Zheng et al, 2019; Wu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%